Sustainable behavior in the fishing cards digital game: a comparative analysis across extraction patterns - de Oliveira, Marlon Alexandre; Ribeiro, Giovan Willian; Couto, Kalliu Carvalho; de Rose, Julio C. (Frontiers in Psychology, 2025)
Sustainability is achieved when resources are used to meet current needs without compromising their availability for future generations. This study examined fishing behaviors across age groups using the Fishing Cards digital game. Participants (N = 30) played 40 s rounds, using two types of cards to catch fish: one less powerful and the other with greater capacity for resource extraction. The game consisted of two phases. In Phase 1, resources were unlimited, allowing participants to fish freely. In Phase 2, resources were limited and could be depleted, potentially leading to defeat in the game. The research aimed to examine whether InterResponse Time (IRT) for fishing responses changed and how card selection patterns and resource availability influenced participants’ choices. Specifically, the goal was to observe how players achieved sustainability in Fishing Cards when resources became limited. Statistical analysis was conducted using Generalized Linear Mixed Models (GLMM). Findings showed a reduction in the selection of the most powerful card and an increase in IRT during the limited resource phase, indicating more sustainable extraction patterns. As resource availability decreased, participants were less likely to use the most powerful cards. The study contributes to understanding sustainable behavior in experimental analogs and highlights the potential of digital gaming for environmental education and sustainability. Limitations are acknowledged.